2017
DOI: 10.1371/journal.pone.0168980
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Effects of Jiang Tang Xiao Ke Granule via PI3K/Akt Signalling Pathway in Type 2 Diabetes KKAy Mice

Abstract: Jiang Tang Xiao Ke (JTXK) granule, a Chinese herbal formula, has been used clinically to treat type 2 diabetes (T2DM) for decades. Our previous studies showed that JTXK granule exhibited anti-diabetic and anti-oxidative functions in experimental diabetic rats induced by a high fat diet and streptozotocin. However, the underlying mechanisms remain poorly understood. Herein, we aimed to investigate the therapeutic effect of JTXK granule on T2DM KKAy mice and the possible associations with skeletal muscle in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 41 publications
1
30
1
1
Order By: Relevance
“…On the other hand, PI3K is a downsignaling molecule in the insulin cascade which is known to enhance glucose uptake through GLUT4 mRNA expression and translocation. [30] Although, we have observed an increase in PI3K mRNA expression with metformin and pioglitazone, as also reported by others, [31,32] the same was not observed with our set of compounds (5a-d). Compounds 5a, 5b, 5c and 5d enhanced glucose uptake by increasing PPAR-γ mRNA expression by approximately 1.…”
Section: Biological Studiessupporting
confidence: 88%
See 2 more Smart Citations
“…On the other hand, PI3K is a downsignaling molecule in the insulin cascade which is known to enhance glucose uptake through GLUT4 mRNA expression and translocation. [30] Although, we have observed an increase in PI3K mRNA expression with metformin and pioglitazone, as also reported by others, [31,32] the same was not observed with our set of compounds (5a-d). Compounds 5a, 5b, 5c and 5d enhanced glucose uptake by increasing PPAR-γ mRNA expression by approximately 1.…”
Section: Biological Studiessupporting
confidence: 88%
“…At stirring isopropyl bromide (0.325 mL, 3.46 mmol) was added slowly, after 5 min the mixture was strongly self-heated As the magnesium turnings were finished, benzo[d]thiazole (0.285 mL, 2.6 mmol) was added to the reaction mixture at 0°C slowly and stirring was continued for [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] min at the same temperature. The flask was pre-heated under vacuum to activate the magnesium and anhydrous THF (25 mL) was added.…”
Section: 6-anhydro-3457-tetra-o-benzyl-1-c-(2-benzo[d]thiozole)-mentioning
confidence: 99%
See 1 more Smart Citation
“…Its expression is decreased by the activation of insulin signaling pathway and facilitated by the increase in the protein expression of tumor necrosis factor-␣ (TNF-␣) in skeletal muscle (51)(52)(53). KKAy mice have been reported to show decreased proteins level of insulin signaling pathway and increased mRNA expression of TNF-␣ in skeletal muscle (54)(55)(56). Therefore, it was suggested that KKAy mice might upregulate the expression of Atrogin1 in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 The lower levels of IRS-1 and PI3K in insulin signal transduction pathway with defects were found in T2DM. 37 Peroxisome proliferatoractivated receptor gamma (PPAR gamma) can enhance insulin sensitivity in muscle and adipose tissues, and some of exogenous potent PPARg ligands are used as medicines to T2DM. 38 p38-MAPK can regulate glucose metabolism.…”
Section: Assay Of Insulin Sensitivity Signaling Pathway Proteinsmentioning
confidence: 99%